2021
DOI: 10.1093/hmg/ddab026
|View full text |Cite
|
Sign up to set email alerts
|

Dominant monoallelic variant in the PAK2 gene causes Knobloch syndrome type 2

Abstract: Knobloch syndrome is an autosomal recessive phenotype mainly characterized by retinal detachment and encephalocele caused by biallelic pathogenic variants in the COL18A1 gene. However, there are patients clinically diagnosed as Knobloch syndrome with unknown molecular etiology not linked to COL18A1. We studied an historical pedigree (published in 1998) designated as KNO2 (Knobloch type 2 syndrome with intellectual disability, autistic behavior, retinal degeneration, encephalocele). Whole exome sequencing of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
1
21
2
Order By: Relevance
“…Furthermore, even though PAK2 variations are mostly associated with ASD, the number of cases described at present is not sufficient to get a precise idea of the extent of clinical consequences. For example, the PAK2 mutation associated with KNO2 syndrome (Antonarakis et al, 2021) already differs from previous descriptions 10. 3389/fnins.2023.1123784 of PAK2 clinical cases that were exclusively associated with ASD.…”
Section: Clinical Overview Of Pak Variantsmentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, even though PAK2 variations are mostly associated with ASD, the number of cases described at present is not sufficient to get a precise idea of the extent of clinical consequences. For example, the PAK2 mutation associated with KNO2 syndrome (Antonarakis et al, 2021) already differs from previous descriptions 10. 3389/fnins.2023.1123784 of PAK2 clinical cases that were exclusively associated with ASD.…”
Section: Clinical Overview Of Pak Variantsmentioning
confidence: 71%
“…Clinical studies reported ASD in patients bearing PAK2 missense mutations or with PAK2 deletions, causing PAK2 haploinsufficiency (Wang et al, 2018). One missense p.(Glu435Lys) variation was recently identified by exome sequencing in two siblings displaying a Knobloch-like syndrome designated as KNO2 with ID, autistic behavior, retinal degeneration, and encephalocele (Antonarakis et al, 2021).…”
Section: Pak2 Variants Are Associated With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…While many cases of KNO are caused by variants in COL18A1, diagnosed as Knobloch syndrome type 1 (KNO1, MIM:120328), other individuals with clinically diagnosed KNO have been identified who lack variants in this gene. 1 Recently, PAK2 was identified as a candidate gene for autosomal dominant Knobloch syndrome type 2 (KNO2; MIM:618458), which has similar features to KNO1. 1 PAK2 is a member of the p21-activated kinase (PAK) family proteins, which are serine/threonine kinases involved in signal transduction, cytoskeletal dynamics, cell cycle progression, and cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, PAK2 was identified as a candidate gene for autosomal dominant Knobloch syndrome type 2 (KNO2; MIM:618458), which has similar features to KNO1. 1 PAK2 is a member of the p21-activated kinase (PAK) family proteins, which are serine/threonine kinases involved in signal transduction, cytoskeletal dynamics, cell cycle progression, and cell motility. 2,3 There are two subfamilies of PAK proteins based on structure, regulation, and sequence identity.…”
Section: Introductionmentioning
confidence: 99%